Clinical characteristics and outcomes of pregnant women with COVID‐19 and comparison with control patients: A systematic review and meta‐analysis. (2nd January 2021) - Jafari, Maryamsadat; Pormohammad, Ali; Sheikh Neshin, Saeideh Aghayari; Ghorbani, Saied; Bose, Deepanwita; Alimohammadi, Shohreh; Basirjafari, Sedigheh; Mohammadi, Mehdi; Rasmussen‐Ivey, Cody; Razizadeh, Mohammad Hossein; Nouri‐Vaskeh, Masoud; Zarei, Mohammad
Summary: In a large‐scale study, 128176 non‐pregnant patients (228 studies) and 10000 pregnant patients (121 studies) confirmed COVID‐19 cases included in this Meta‐Analysis. The mean (confidence interval [CI]) of age and gestational age of admission (GA) in pregnant women was 33 (28–37) years old and 36 (34–37) weeks, respectively. Pregnant women show the same manifestations of COVID‐19 as non‐pregnant adult patients. Fever (pregnant: 75.5%; non‐pregnant: 74%) and cough (pregnant: 48.5%; non‐pregnant: 53.5%) are the most common symptoms in both groups followed by myalgia (26.5%) and chill (25%) in pregnant and dysgeusia (27%) and fatigue (26.5%) in non‐pregnant patients. Pregnant women are less probable to show cough (odds ratio [OR] 0.7; 95% CI 0.67–0.75), fatigue (OR: 0.58; CI: 0.54–0.61), sore throat (OR: 0.66; CI: 0.61–0.7), headache (OR: 0.55; CI: 0.55–0.58) and diarrhea (OR: 0.46; CI: 0.4–0.51) than non‐pregnant adult patients. The most common imaging found in pregnant women is ground‐glass opacity (57%) and in non‐pregnant patients is consolidation (76%). Pregnant women have higher proportion of leukocytosis (27% vs. 14%), thrombocytopenia (18% vs. 12.5%) and have lower proportion of raised C‐reactive protein (52% vs. 81%) compared with non‐pregnant patients. Leucopenia and lymphopenia are almost the same in both groups. The most common comorbidity in pregnant patients is diabetes (18%) and in non‐pregnant patients is hypertension (21%). Case fatality rate (CFR) of non‐pregnant hospitalized patients is 6.4% (4.4–8.5), and mortality due to all‐cause for pregnant patients is 11.3% (9.6–13.3). Regarding the complications of pregnancy, postpartum hemorrhage (54.5% [7–94]), caesarean delivery (48% [42–54]), preterm labor (25% [4–74]) and preterm birth (21% [12–34]) are in turn the most prevalent complications. Comparing the pregnancy outcomes show that caesarean delivery (OR: 3; CI: 2–5), low birth weight (LBW) (OR: 9; CI: 2.4–30) and preterm birth (OR: 2.5; CI: 1.5–3.5) are more probable in pregnant woman with COVID‐19 than pregnant women without COVID‐19. The most prevalent neonatal complications are neonatal intensive care unit admission (43% [2–96]), fetal distress (30% [12–58]) and LBW (25% [16–37]). The rate of vertical transmission is 5.3% (1.3–16), and the rate of positive SARS‐CoV‐2 test for neonates born to mothers with COVID‐19 is 8% (4–16). Overall, pregnant patients present with the similar clinical characteristics of COVID‐19 when compared with the general population, but they may be more asymptomatic. Higher odds of caesarean delivery, LBW and preterm birth among pregnant patients with COVID‐19 suggest a possible association between COVID‐19 infection and pregnancy complications. Low risk of vertical transmission is present, and SARS‐CoV‐2 can be detected in all conception products, particularly placenta and breast milk. Interpretations of these results should be done cautiously due to the heterogeneity between studies; however, we believe our findings can guide the prenatal and postnatal considerations for COVID‐19 pregnant patients.